DUKUNGAN KELUARGA BERPENGARUH TERHADAP SKRINING ANTENATAL BIDAN DESA - Ribkha Itha Idhayanti; Masini Masini; Bambang Sarwono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
Based on the results of the initial survey in Magelang district health center 80% of midwives do not perform in accordance with the standard practice of antenatal this strengthens the case investigators that good antenatal screening practices should get good support, especially from leaders, friends and family midwife. This research method is an explanatory research approach contingentcy crosectional coefficient. The population in this study was a midwife in Magelang district some 80 people. Sample with slovin formula showed 30 respondents . Samples were obtained by proportional random sampling. The sample came from the area Temangung results showed the majority of practicing midwives in antenatal screening in good categories 56.2%. The research method used by researchers to obtain data is a questionnaire for the free variable and observational support by using the checklist for the dependent variable high risk antenatal screening practices. Based on the analysis, this study concludes that: the support of the family, especially the husband was very influential on antenatal screening by village midwife friend . Also support profession, especially in terms of information about the practice of antenatal discussion particularly high risk antenatal screening, the higher the support of family and friends profession , make practice screening antenatal midwife better. Proven support has significant influence on the practice of antenatal screening midwife is 60% support profession friends with p value of 0.021 and support family midwives 75% with p value 0.027.